(untitled) (Global Journal of Management and Business Research, 2024)
This research delves into the intricate economic repercussions of Brexit on migrant entrepreneurs and host rural communities in Scotland Data collection employed a combination of 275 questionnaires distributed across 10 rural areas and in-depth insights drawn from a total of six focus group discussions Specifically three focus groups were conducted with migrant entrepreneurs operating businesses in rural areas offering a profound exploration of their unique challenges experiences and perspectives Additionally three separate focus groups were conducted with the host communities encompassing rural residents and third-party stakeholders including local government representatives and community organizations The questionnaire yielded responses from a diverse sample with 115 valid responses after rigorous data cleaning The research utilizes a mixed-methods approach intertwining quantitative and qualitative analyses The quantitative analysis employs a non-parametric Kruskal-Wallis H test to examine the disparities in perceptions of Brexit s economic impact between migrant entrepreneurs and host rural communities across the 10 surveyed rural areas